Influence of the Morphology of ZnO Nanostructures on Luminescent and Photovoltaic Properties - Ibrayeva, N. Kh.; Ilyassov, B. R.; Afanasyev, D. A. (SPRINGER, 2017)
Arrays of ZnO nanorods and nanoplates are synthesized by the hydrothermal and electrochemical methods, respectively. The photoluminescence spectra indicate that the nanoplates have a more defective structure than the nanorods. The obtained ZnO nanostructures are used as the basis to construct dye-sensitized solar cells. The influence of morphology and defectiveness of ZnO nanostructures on the luminescent and photovoltaic properties of the cells is studied.